Globalization and growth of US university patenting (2009–2014). (August 2016) - Leydesdorff, Loet; Etzkowitz, Henry; Kushnir, Duncan
Following a pause, with a relatively flat rate, from 1998 to 2008, the long-term trend of university patenting rising as a share of all patenting has resumed, driven by the internationalization of academic entrepreneurship and the persistence of US university technology transfer. The authors disaggregate this recent growth in university patenting at the US Patent and Trademark Organization (USPTO) in terms of nations and patent classes. Foreign patenting in the United States almost doubled during the period 2009–2014, mainly due to patenting by universities in Taiwan, Korea, China and Japan. These nations compete with the United States in terms of patent portfolios, whereas most European countries – with the exception of the United Kingdom – have more specific portfolios, mainly in biomedical fields. In the case of China, Tsinghua University holds 63% of the university patents in USPTO; followed by King Fahd University with 55.2% of the national portfolio.